Static and dynamic wireless charging system for electric vehicle - Jithin, Antony; Sasi, Akshath; Jaison, Chris; Bensen, A. J.; Reghuraj, A. R. (Recent Research in Science and Technology, 2023)
Electrified transportation will help to reduce greenhouse gas emissions and petrol prices. Electrified transportation demands that a wide variety of charging networks be set up, in a user-friendly environment, to encourage adoption. Wireless electric vehicle charging systems (WEVCS) can be a potential alternative technology to charge electric vehicles (EVs) without any plug-in problems. This paper outlines the currently available wireless power transfer technology for EVs. In addition, it also includes wireless transformer structures with a variety of ferrite shapes, which have been researched. WEVCS are associated with health and safety issues, which have been discussed with the current development in international standards. Two major applications, static and dynamic WEVCS, are explained, and up-to-date progress with features from research laboratories, universities, and industries is recorded. Moreover, future upcoming concepts-based WEVCS, such as ‘‘vehicle-to-grid (V2G)” and ‘‘in-wheel” wireless charging systems (WCS) are reviewed and examined, with qualitative comparisons with other existing technology.